2019
DOI: 10.1016/j.devcel.2019.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Stimulates Cardiomyocyte Proliferation and Controls Organ Size and Regeneration in Zebrafish

Abstract: Attaining proper organ size during development and regeneration hinges on the activity of mitogenic factors. Here, we performed a large-scale chemical screen in embryonic zebrafish to identify cardiomyocyte mitogens. Although commonly considered antiproliferative, vitamin D analogs like alfacalcidol had rapid, potent mitogenic effects on embryonic and adult cardiomyocytes in vivo. Moreover, pharmacologic or genetic manipulation of vitamin D signaling controlled proliferation in multiple adult cell types and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
113
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(118 citation statements)
references
References 70 publications
(80 reference statements)
5
113
0
Order By: Relevance
“…Several studies have demonstrated that the ErbB pathway plays a promotive role in the regeneration of other tissues. For example, mutations in erbb2 or erbb3 cause a deficiency in caudal fin regeneration (26), and AG1478 treatment inhibits the regenerative proliferation of cardiomyocytes (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that the ErbB pathway plays a promotive role in the regeneration of other tissues. For example, mutations in erbb2 or erbb3 cause a deficiency in caudal fin regeneration (26), and AG1478 treatment inhibits the regenerative proliferation of cardiomyocytes (25).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of ErbB signaling has been implicated in the regeneration of other tissues (25,26), so we investigated whether ErbB pathway inhibition could improve hair cell regeneration in the three mutants that disrupt regeneration. In performing the hair cell regeneration assay in the presence of the ErbB inhibitor, AG1478 had no obvious effect on the regeneration of hair cells in control siblings, however, it did exhibit a dose-dependent rescue of regeneration in all three mutants ( Fig.…”
Section: Erbb Pathway Inhibition Partially Rescues Hair Cell Regeneramentioning
confidence: 99%
“…It is reported recently that in zebrafish, VDR activation stimulates CM proliferation, while VDR antagonism reduces CM proliferation and compromises cardiac regeneration 30 . This sharply contrasts with VDR signaling in mammals, which seems to exert broadly anti-proliferative effects [27][28][29] , as corroborated by our in vitro observations.…”
Section: Discussionmentioning
confidence: 99%
“…Antiproliferative effects of vitamin D analogs have been reported in mammalian cells generally 27 and mammalian CMs and CM-derived cell lines specifically 28,29 . However, vitamin D analogs alfacalcidol and calcipotriene significantly increase CM proliferation in embryonic zebrafish, whereas VDR-inhibitor PS121912 significantly decreases CM proliferation 30 . Alfacalcidol also stimulates CM proliferation in adult zebrafish during heart regeneration, while VDR suppression decreases CM proliferation during regeneration 30 .…”
mentioning
confidence: 97%
“…Several articles in the last decade have reported increased cell cycle activity through the overexpression or suppression of various purported regulators of the cardiomyocyte cell cycle, reviewed elsewhere (14)(15)(16)(17)(18). Suppression of the Hippo pathway with constitutively active Yap1 increased cardiomyocyte proliferation without increasing cardiomyocyte size (10), and improved heart function after myocardial infarction (19).…”
Section: Introductionmentioning
confidence: 99%